On the dynamics and function of ciliates in sequencing batch biofilm reactors - Fried, J (Water science and technology : a journal of the International Association on Water Pollution Research, 2003)
Ciliates are known to directly influence the performance of wastewater treatment plants mainly by feeding on suspended particles. By monitoring two lab-scale sequencing batch biofilm reactors (SBBR), one filled with expanded shale (clay spheres), the other with "Kaldnes" particles (PE-carriers), the succession of biofilm communities with special emphasis on ciliates was monitored for one year. Ciliates were identified and quantified at the species level and compared to rotifer and nematode abundances. Members of the subclass Peritrichia clearly dominated the community of protozoa. Epistylis cf. coronata and Opercularia asymmetrica were the dominant species within this group. The tree-like structure of their colonies provided a distinctive augmentation of the area available for bacterial colonization. The flux of water, produced by E. cf. coronata due to cilia motility, has been visualized and measured by video processing. This flux of water was still measurable at distances > 500 microm and maximum water currents raised up to 180 microm s(-1). Therefore, the role of ciliates is not only restricted to the ingestion of bacteria and suspended particles. They also alter water flux and carry nutrients to the inner parts of the biofilm. Thus, monitoring biofilm formation in wastewater treatment plants should always consider the impact of protists such as ciliates